OUR EXPERIENCE OF OPTIMIZATION AND LEGITIMIZATION OF HEART TEAM WORK (MEDICAL CONSULTATION FOR DETERMINATION OF TREATMENT MANAGEMENT IN PATIENTS WITH ISCHEMIC HEART DISEASE) - M. Yu. Kaputin; A. V. Biryukov; V. Yu. Ul’Chenko (Вестник хирургии имени И.И. Грекова, 2016)
The article raises the problem of optimization and legitimization of work of the Heart Team. It also described the background and international experience, provided an overview of the recent international guidelines in relation to management of revasculization in patients with stable coronary artery disease. The article presents an experience of the I. P.Pavlov First Saint-Petersburg State Medical University.